EFFICACY OF TAP BLOCK AND PLACEBO FOR PAIN IN PATIENTS UNDERGOING CSECTION SURGERY - Khalid, Usman; Majeed, Kaukab; Yasmeen, Maihmoona; Mehmood, Khalid; Muazzam, Muhammad Ali; Rehmani, Jawad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare efficacy of transversus abdominis plane block and placebo for pain in patients undergoing C-section surgery.Study Design: Comparative cross-sectional study.Place and Duration of Study: Department of Anaesthesiology, Combined Military Hospital Quetta, from Apr toOct 2018.Methodology: A sample size of 200 patients calculated by WHO calculator undergoing Elective C-section andof age 20-40 year were randomized in a double blind study to undergo transversus abdominis plane block orplacebo group in two equal groups. Group A received block as placebo and group B with Bupivacaine. Resultsrecorded and analysed there-after for conclusion.Results: The mean age of patients in group A was 29.98 ± 5.18 years and in group B was 29.68 ± 5.43 years (pvalue ≤0.01). Majority of the patients 141 (70.50%) were between 31 to 40 years of age. Out of 200 patients, 108 (54.0%) were ASA I and 92 (46.0%) were ASA II (p-value ≤0.01). Mean body mass index was 25.20 ± 2.28 kg/m2 (p-value ≤0.01). Meantime for the first analgesia in the patients undergoing elective C-section in group A (placebo group) was 4.96 ± 1.44 hours while in group B (transversus abdominis plane block group) was 11.24 ± 1.83 hours (p-value ≤0.01).Conclusion: This study concluded that meantime for the first analgesia was found longer in TransversusAbdominis plane block for post-operative pain management in patients undergoing elective C-section.